MADURA FOLKTALES: TOWARD THE UNIVERSALITIES - Harits, Imron Wakhid (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Abstract. Madura Island has myriads of folktales as a result of its acculturation since the prosperous of Hinduism kingdom till the glorious of Islamic Mataram era. These notions are interested to examine. This paper probes the native of Madura folktales along with their uniqueness and link it with the universality of the folktales in the world. By investigating the motifs, Madura Folktales engage with other folktales across nation and it is really meaningful in the children literature perspective. The children literature mediates the wonder folktales such as Madura folktales into the ideal of children literature viewpoints. Keywords: Madura Folktales, wonder folk/fairy tales, children literature